2020
DOI: 10.1002/pchj.405
|View full text |Cite
|
Sign up to set email alerts
|

Development of orientation sensitivity to Chinese compound characters in 4‐ to 6‐year‐ old children

Abstract: Visual‐orthographic skill is crucial to beginning readers when they learn to read. Confusion of the orientation of letters or words is common for beginning readers across different writing systems, especially for Chinese script with high visual complexity. The present study aims to explore children's early development of Chinese compound characters' orientation perception and its relation to their reading development. Ninety‐two preschool children aged from 4 to 6 years participated in the study. They were ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Thus, although symmetrical character learning was significantly correlated with Chinese word reading and word writing at both time points, it was not uniquely associated with them after age, IQ, and autoregressive effects were statistically controlled. From a novel perspective of symmetry sensitivity, this study contributes to current literature on the associations between breaking mirror invariance in print (such as shape orientation sensitivity) and literacy acquisition by showing that such link manifests not only in reading (Fernandes et al, 2016;Zhang et al, 2021) but more particularly in writing. This study also adds to the recent demonstrations by Fischer and Luxembourger (2022) of the difference between a recognition task (e.g., distinguishing between the reversible letters of b and d) and a writing task (e.g., reversing letters or digits in writing), the two tasks often considered as equivalent in the literature on mirror invariance but actually found to be at least partly independent processes (having a negative relationship between the two rates) in French 6 year olds.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Thus, although symmetrical character learning was significantly correlated with Chinese word reading and word writing at both time points, it was not uniquely associated with them after age, IQ, and autoregressive effects were statistically controlled. From a novel perspective of symmetry sensitivity, this study contributes to current literature on the associations between breaking mirror invariance in print (such as shape orientation sensitivity) and literacy acquisition by showing that such link manifests not only in reading (Fernandes et al, 2016;Zhang et al, 2021) but more particularly in writing. This study also adds to the recent demonstrations by Fischer and Luxembourger (2022) of the difference between a recognition task (e.g., distinguishing between the reversible letters of b and d) and a writing task (e.g., reversing letters or digits in writing), the two tasks often considered as equivalent in the literature on mirror invariance but actually found to be at least partly independent processes (having a negative relationship between the two rates) in French 6 year olds.…”
Section: Discussionmentioning
confidence: 68%
“…For example, to correctly identify a word, children need to develop print-specific understanding that symmetrical images of d and b are two different letters. Sensitivity to spatial orientation has been found to significantly relate to reading skills in English-reading first graders (Fernandes et al, 2016) and Chinese-reading 6-year-olds (Zhang et al, 2021). Compared with early word reading, there is less report on the association between sensitivity to symmetry in print and early word writing.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have found that this phenomenon is closely related to the orientation knowledge of letters or words (Ahr et al, 2016; Dehaene et al, 2010; Fernandes et al, 2016). Crucially, significant associations between orientation knowledge of letters or words and reading ability in young children have been supported by some evidence (Badian, 2005; Fernandes et al, 2016; Lomax and McGee, 1987; McBride-Chang and Suk-Han Ho, 2005; Zhang and Li, 2018; Zhang et al, 2021b). While a number of recent researches have focused on the orientation knowledge of letters or words (Ahr et al, 2016; Dehaene et al, 2010; Fernandes et al, 2016; Lomax and McGee, 1987), little attention has been paid to the development of orientation sensitivity to Chinese characters in prereaders (Zhang and Li, 2018; Zhang et al, 2021b).…”
Section: Introductionmentioning
confidence: 93%
“…Specifically, it is expected that orientation sensitivity will develop early, with differences between inverted/mirrored pairs and normal pairs found in children of a certain age, based on previous findings from cross-writing systems (e.g., Fernandes et al, 2016; Levy et al, 2006; Miller, 2002; Sun et al, 2022; Zhang and Li, 2018; Zhang et al, 2021b). Importantly, given previous related findings (Blackburne et al, 2014; Davidson, 1935; Fernandes et al, 2016; Zhang and Li, 2018; Zhang et al, 2021b), it is predicted that the contrasting patterns of the two conditions (inverted pairs versus normal pairs; mirrored pairs versus normal pairs) will show differences in children at different ages and that mirrored orientation sensitivity will emerge later. In addition, the contrasting patterns of the two conditions (inverted pairs versus normal pairs; mirrored pairs versus normal pairs) will also show differences in simple Chinese characters and compound Chinese characters, as suggested by the results of adult studies (Li et al, 2022; Luo et al, 2017).…”
Section: The Present Studymentioning
confidence: 99%
“…Both inversion and word length effects have been used in some relevant studies with children. For example, one study demonstrated sensitivity to inverted versus upright compound Chinese characters in 4‐year‐old children, whereas 6‐year‐olds were sensitive to mirrored compound characters (Zhang et al., 2021). Word length effects also differed across age with second‐graders revealing a steep slope as a function of length (approximately 50 ms/letter), and college students showing a negligible effect of word length (Samuels et al., 1978).…”
Section: Introductionmentioning
confidence: 99%